2022
DOI: 10.1101/2022.12.07.519490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The structure of a human translation initiation complex reveals two independent roles for the helicase eIF4A

Abstract: Canonical initiation of translation in eukaryotes involves recruitment of the 43S pre-initiation complex to the 5′ end of mRNA by the cap-binding complex eIF4F to form the 48S initiation complex (48S), followed by scanning along the mRNA until the start codon is selected. We had previously shown that eIF4F binds near the mRNA channel exit site of the 43S. Here we describe a human 48S positioned at the start codon which reveals a second molecule of eIF4A at the mRNA entry site and provides a mechanism for how i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…Recombinant full-length eIF4G is notoriously difficult to purify and possesses potent non-specific RNA binding activity 30,35 . Consequently, many biochemical studies have been performed with truncated eIF4G constructs 14,15,19,23,24,26,[36][37][38][39] together with short, minimal-length mRNA mimics to minimize nonspecific binding 15,24,30,38,39 . Biochemical studies have also been hampered by the lack of a complete structure of eIF4F 13,14,27,38 .…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant full-length eIF4G is notoriously difficult to purify and possesses potent non-specific RNA binding activity 30,35 . Consequently, many biochemical studies have been performed with truncated eIF4G constructs 14,15,19,23,24,26,[36][37][38][39] together with short, minimal-length mRNA mimics to minimize nonspecific binding 15,24,30,38,39 . Biochemical studies have also been hampered by the lack of a complete structure of eIF4F 13,14,27,38 .…”
Section: Introductionmentioning
confidence: 99%
“…While we were finalizing this manuscript a structure of human 48S PIC was reported where a low-resolution density in the vicinity of the mRNA channel entry on the solvent-exposed side is tentatively assigned to eIF4B (Brito Querido et al, 2022). Overall, the structural analysis presented in this study shows how yeast eIF4B helps in mRNA recruitment as well as scanning during translation initiation.…”
Section: Discussionmentioning
confidence: 74%
“…Based on our observations and comparison of 40S-eIF4B with reported structures of partial yeast 43S and 48S PICs, were have proposed a model explaining the events that may happen during mRNA recruitment to the small ribosomal subunit in yeast (Figure 5). While we were finalizing this manuscript a structure of human 48S PIC was reported where a low-resolution density in the vicinity of the mRNA channel entry on the solvent-exposed side is tentatively assigned to eIF4B (Brito Querido et al ., 2022). Overall, the structural analysis presented in this study shows how yeast eIF4B helps in mRNA recruitment as well as scanning during translation initiation.…”
Section: Resultsmentioning
confidence: 99%
“…We found that eIF4A and ASCC3 regulate similar transcripts and phenotypic exacerbation was observed in response to the loss of ASCC3 in combination with eIF4A depletion. Previous cryo‐EM analysis has shown that eIF4A functions at a position near the mRNA exit channel of the 40S ribosome subunit (Querido et al , 2020), but a recent study has identified a second eIF4A that binds to the mRNA entry channel, in addition to the one that is part of eIF4F, which likely functions to unwind the secondary structure of mRNAs that enter the mRNA entry channel during scanning (preprint: Querido et al , 2022). The low helicase activity of eIF4A compared with many other helicases suggested that additional helicases may be required to scan the 5′‐UTR of mRNAs with highly stable secondary structures, and ASCC3 may be one of them for a subset of transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…C Metagene plots for full-length footprints obtained by TCP-seq analysis of the SSU fraction prepared from control, eIF4A1/A2 dKD, and ASCC3 KD cells. binds to the mRNA entry channel, in addition to the one that is part of eIF4F, which likely functions to unwind the secondary structure of mRNAs that enter the mRNA entry channel during scanning (preprint: Querido et al, 2022). The low helicase activity of eIF4A compared with many other helicases suggested that additional helicases may be required to scan the 5 0 -UTR of mRNAs with highly stable secondary structures, and ASCC3 may be one of them for a subset of transcripts.…”
Section: Discussionmentioning
confidence: 99%